Compensation and Work Life Balance on Turnover Intention: The Mediating Role of Employee Satisfaction at PT. Graha Inti Jaya - Rima Yhanti; Nurul Hermina (Dinasti International Journal of Education Management and Social Science, 2025)
The high turnover intention at PT. Graha Inti Jaya reflects challenges in human resource management, particularly regarding compensation, work-life balance, and job satisfaction. This study examines the influence of compensation and work-life balance on turnover intention, with job satisfaction as a mediating variable. A quantitative approach was employed through a survey of 144 respondents drawn from 225 employees. Data were analysed using structural equation modelling with Partial Least Squares. The findings indicate that compensation positively affects job satisfaction and negatively affects turnover intention. In contrast, work-life balance negatively influences job satisfaction and positively influences turnover intention. Job satisfaction itself negatively impacts turnover intention and mediates the relationship between compensation and turnover intention, but not between work-life balance and turnover intention. These results highlight that compensation plays a crucial role in enhancing job satisfaction and reducing turnover intention. Conversely, poor work-life balance can diminish satisfaction and increase employees’ desire to leave. Companies are encouraged to design fair and transparent compensation systems while revising work-life balance policies to better align with employee expectations. By addressing these factors, organizations can strengthen employee commitment and reduce turnover risks.